Mechanosensation and Mechanotransduction in Natural Killer Cells - Santoni, Giorgio; Amantini, Consuelo; Santoni, Matteo; Maggi, Federica; Morelli, Maria Beatrice; Santoni, Angela (Frontiers in Immunology, 2021)
Natural killer (NK) cells are a main subset of innate lymphocytes that contribute to host immune protection against viruses and tumors by mediating target cell killing and secreting a wide array of cytokines. Their functions are finely regulated by a balance between activating and inhibitory receptors and involve also adhesive interactions. Mechanotransduction is the process in which physical forces sensed by mechanosensors are translated into chemical signaling. Herein, we report findings on the involvement of this mechanism that is mainly mediated by actin cytoskeleton, in the regulation of NK cell adhesion, migration, tissue infiltration and functions. Actin represents the structural basis for NK cell immunological synapse (NKIS) and polarization of secretory apparatus. NK-target cell interaction involves the formation of both uropods and membrane nanotubes that allow target cell interaction over long distances. Actin retrograde flow (ARF) regulates NK cell signaling and controls the equilibrium between activation versus inhibition. Activating NKIS is associated with rapid lamellipodial ARF, whereas lower centripetal actin flow is present during inhibitory NKIS where β actin can associate with the tyrosine phosphatase SHP-1. Overall, a better knowledge of mechanotransduction might represent a future challenge: Realization of nanomaterials tailored for NK cells, would be important to translate in vitro studies in in vivo new immunotherapeutic approaches.